2007
DOI: 10.1111/j.1540-8175.2007.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐Mediated Dilation and Gender in Patients with Coronary Artery Disease: Arterial Size Influences Gender Differences in Flow‐Mediated Dilation

Abstract: Males and postmenopausal females with CAD show differences in endothelium-dependent vasodilatation that seem to secondarily result from differences in the BAd. Objective comparison of %FMD is only possible between patients with the same brachial artery size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 23 publications
3
25
1
Order By: Relevance
“…18 Brachial artery size is an important consideration, given that FMD has been found inversely related to BA dimension. 19 Decreased PWV decline in the present study is similar to that previously observed in patients with congestive heart failure. 13 The earlier recovery of PWV to baseline in the HT group may be related to the initial lesser decline in PWV or to a prolonged vasodilatory response.…”
Section: Discussionsupporting
confidence: 92%
“…18 Brachial artery size is an important consideration, given that FMD has been found inversely related to BA dimension. 19 Decreased PWV decline in the present study is similar to that previously observed in patients with congestive heart failure. 13 The earlier recovery of PWV to baseline in the HT group may be related to the initial lesser decline in PWV or to a prolonged vasodilatory response.…”
Section: Discussionsupporting
confidence: 92%
“…When differences in D base are properly adjusted for, the 'corrected' FMD% is 3.5% (4.2) in women and 4.4% (4.2) in men, completely contrary to the FMD% results. In contrast to recent suggestions, 25 women in the MESA do not have better endothelial function than men across most age categories (Figure 3). Researchers may adjust FMD% for various potential covariates but this approach might be in vain if FMD% is the inappropriate outcome to select in the first place.…”
Section: Sex and Age Differences In The Flowmediated Responsecontrasting
confidence: 99%
“…And it is a common practice amongst researchers on FMD% to test whether there are statistically significant differences between groups or repeated measures in D base . 25 First, even in placebo-controlled and randomised studies, checking whether baseline measurements differ significantly between samples is known to be an unsound and illogical approach to the analysis of change because a lack of significant difference cannot be treated as a proof of equivalence. 10,11,23 Indeed, in a randomised trial one should not test for pre-intervention differences statistically, as any observed baseline imbalance must be due to chance, by definition.…”
Section: Significance Testing For D Base Stabilitymentioning
confidence: 99%
“…In contrast, smaller arteries appear to dilate more than (51), because postischemic systolic flow depends on the squared radius of the vessel, and therefore hyperemic shear stress is greater in small arteries (52). FMD values have gender differences that might in part be a result of differences in baseline artery diameters (53). In addition, sympathetic activation, at a clinically relevant range, has a profound effect on the FMD response through an α adrenergic mechanism (54).…”
Section: Limitationsmentioning
confidence: 99%